Pelatihan Membangun Merek dengan Pemasaran yang Berorientasi pada Manusia Sebagai Daya Tarik pada Ikatan Remaja RW 07 Margonda, Depok, Provinsi Jawa Barat - Basudani, Wahid Akbar; Abdullah, Muhammad; Zuniarti, Ida; Simamora, Valentine Theresia (Indonesian Journal of Society Engagement, 2023)
This Community Service activity aims to provide training for teenagers who are members of the RW 007 Margonda Youth Association organization, Depok, West Java, where these teenagers need knowledge about how to build a brand in entrepreneurship. Current developments in the era of digitalization mean that consumers can communicate easily by social media, which requires business owners to build a brand that is human-oriented. Building a brand that is oriented towards humans as customers can be done by understanding consumers through social listening, netnography and empathic research methods. By knowing the concept of building a human-oriented brand, these teenagers can easily capture consumer responses and innovate products according to their customers' needs.